El periodismo móvil aplicado en medios de comunicación digital. Caso ND noticias - Cordova Moreira, Livinstong Gustavo (2022)
Technological advances have generated changes in the way society interacts. The data unfolds amid the rise of new information and communication technologies (NICT), therefore, journalists must adapt to these changes, so that the transformation of journalism arises. This work focuses on analyzing the development of mobile journalism in the digital medium ND Noticias. The methodology based on the inductive study plan, allowed to obtain qualitative results, through interviews and observation sheets to the established digital communication medium, which applies mobile journalism systematically. It seeks to generate knowledge in students and future communicators about the new information-generating tools in the journalistic context, with the development of research on mobile journalism, the applications with the highest rate of downloads, the adaptation of journalists, and their impact on society.